2018
DOI: 10.3389/fenrg.2018.00019
|View full text |Cite
|
Sign up to set email alerts
|

Probing Stress States in Silicon Nanowires During Electrochemical Lithiation Using In Situ Synchrotron X-Ray Microdiffraction

Abstract: Silicon is considered as a promising anode material for the next-generation lithium-ion battery (LIB) due to its high capacity at nanoscale. However, silicon expands up to 300% during lithiation, which induces high stresses and leads to fractures. To design silicon nanostructures that could minimize fracture, it is important to understand and characterize stress states in the silicon nanostructures during lithiation. Synchrotron X-ray microdiffraction has proven to be effective in revealing insights of mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…2(a) below. The crystalline cores of the SiNWs are conical in shape, in line with the morphological study presented in our earlier report [31] and by Yang et al [28]. The conical shape of the crystalline cores is due to the nonuniform lithiation along the length of the nanowires, reducing from the tip to the root [28].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…2(a) below. The crystalline cores of the SiNWs are conical in shape, in line with the morphological study presented in our earlier report [31] and by Yang et al [28]. The conical shape of the crystalline cores is due to the nonuniform lithiation along the length of the nanowires, reducing from the tip to the root [28].…”
Section: Resultssupporting
confidence: 87%
“…In this article, direct in situ stress measurement was performed using synchrotron X-ray microdiffraction as explained in the following sections. Compared to our recent earlier reports [30,31], the present work reported an enhanced stress study detailing the complete stress states (the deviatoric tensor components) and their evolution during the in situ electrochemical lithiation experiments. Synchrotron X-ray microdiffraction (lSXRD) has been proven to be effective for revealing insights of mechanical stress states and other mechanics considerations (such as plasticity, mechanisms preceding fracture events, or final catastrophic failure) in small-scale crystalline structures in many important technological applications, such as microelectronics [32,33,34,35,36,37], nanotechnology [38,39,40,41], and photovoltaics [37,42,43,44].…”
Section: Introductionmentioning
confidence: 93%
“…A synchrotron operando XRD technique, as presented in Figure 18e, was employed to measure the mechanical strain in thee large-volume-change Ge anodes. I. Ali et al [337] adopted an in situ synchrotron X-ray microdiffraction to measure the stress level in Si nanowires and found that lithiation imported a compressive stress up to −325.5 MPa in the crystalline cores. The compressive strain, driven by the coexistence of two phases (lithiated and unlithiated) in the Ge, was also predicted by an analytical core-shell mechanical mode proposed by the author.…”
Section: Multibeam Optical Stress Sensor (Moss) Techniquementioning
confidence: 99%
“…Although the above-mentioned oxide anode materials have a high fast-charging performance due to their high lithium ion diffusion coefficient (~10 −8 cm 2 /s); they have a common defect of low energy density in full cells, which is caused by their high lithiation potential, as shown in Figure 9. Silicon and silicon-based materials, the new generation of anode materials, have a relatively high gram capacity, but their inherently poor conductivity and their volume expansion in the process of charging and discharging lead to a gradual deterioration of the cycle performance, which is difficult to effectively control in a short period of time [94][95][96]. Academically, the volume expansion problem of Si/SiO can be solved by reserving space, for example, designing core-shell structure, porous structure, and so on.…”
Section: Electrode Materialsmentioning
confidence: 99%
“…Compared with Si/SiO related anode, the advantage of red phosphorus related anode is the platform voltage of discharging is higher with less risk of Li plating and more safety [92]. anode materials, have a relatively high gram capacity, but their inherently poor conductivity and their volume expansion in the process of charging and discharging lead to a gradual deterioration of the cycle performance, which is difficult to effectively control in a short period of time [94][95][96]. Academically, the volume expansion problem of Si/SiO can be solved by reserving space, for example, designing core-shell structure, porous structure, and so on.…”
Section: Electrode Materialsmentioning
confidence: 99%